A survey of youth with new onset type 1 diabetes: Opportunities to reduce diabetic ketoacidosis. Issue 7 (11th October 2016) - Baldelli, Luke; Flitter, Ben; Pyle, Laura; Maahs, David M.; Klingensmith, Georgeanna; Slover, Robert; Alonso, G. Todd
Abstract : Objective: Pediatric patients in Colorado with new onset type 1 diabetes (T1D) presenting with diabetic ketoacidosis (DKA) increased from 29.9% to 46.2% from 1998 to 2012. The purpose of this study was to compare differences between patients with newly diagnosed T1D who presented in DKA with those who did not across three domains: sociodemographic factors, access to medical care, and medical provider factors, aiming to identify potential targets for intervention. Methods: Sixty‐one patients <17 years of age with T1D duration <6 months completed the questionnaire. Groups were compared using Fisher's exact test or the Kruskal‐Wallis test. Results: Parents of 28% of patients researched their child's symptoms on the Internet prior to diagnosis. At the first healthcare visit for symptoms of T1D, 23% were not diagnosed. There were no significant differences between groups (DKA vs non‐DKA) in demographics, first healthcare setting for T1D symptoms, provider type at first visit or at diagnosis, insurance status, or specific barriers to care. DKA patients had a longer interval between previous well visit to diagnosis (median 172 vs 263 days, P = 0.01). Non‐DKA patients were more likely to have blood glucose measured at P = 0.02, and had fewer symptoms prior to ( P = 0.01) the first visit for diabetes symptoms. Parents of non‐DKA patients were more likely to be familiar with symptoms of diabetes ( P < 0.001) and to suspect diabetes ( P = 0.01). Conclusion: Targets for campaigns to prevent DKA include increasing provider glucose and ketone testing, increasing public knowledge about diabetes, and understanding how socio‐demographic factors may delay T1D diagnosis.